2010
DOI: 10.1002/ptr.3167
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of foods on helicobacter pylori growth

Abstract: Eradication of H. pylori can reduce the risk of non-cardia gastric cancer developing in infected humans. Thus, the consumption of foods that inhibit the growth of these bacteria may provide an alternative to current therapies that include antibiotics, proton pump inhibitors and/or bismuth salts. This study describes a simple broth dilution assay developed to screen a range of foods for their individual and combined effects on H. pylori growth. It was found that foods with measurable anti-H. pylori activity hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…However, it is important to emphasise that none of the trial designs is completely relevant to the normal human intake of high health vegetables, such as broccoli. The trials were at doses considerably higher than found in a normal diet, and ignore the effects of the biological matrix [84], as well as potential synergies among different bioactives [51,85]. It is also possible that the regimen was inappropriate, in being a continuous high dose rather than intermittent nutrient intake, which would more accurately reflect the natural diet situation.…”
Section: Proving Efficacy Of Broccoli In Cancer Preventionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it is important to emphasise that none of the trial designs is completely relevant to the normal human intake of high health vegetables, such as broccoli. The trials were at doses considerably higher than found in a normal diet, and ignore the effects of the biological matrix [84], as well as potential synergies among different bioactives [51,85]. It is also possible that the regimen was inappropriate, in being a continuous high dose rather than intermittent nutrient intake, which would more accurately reflect the natural diet situation.…”
Section: Proving Efficacy Of Broccoli In Cancer Preventionmentioning
confidence: 96%
“…Several interacting signalling pathways, including ERK, JNK and MAPK signalling, may be involved in the apoptosis induced by SF and related glucosinolates, as well as flavonoids such as kaempferol [50][51][52][53]. These pathways sense extracellular stresses, leading not only to the induction of Nrf2-mediated transcription (described in Fig.…”
Section: Enhancement Of Apoptosis and Related Eventsmentioning
confidence: 99%
“…In keeping with this, there were no previously recorded data regarding the main sources and also route of transmission of H. pylori into human (7). Several previously published data revealed that H. pylori had a significant prevalence in various types of foods, especially milk, meat, salad, vegetables, and ready to eat foods, which may show the food-borne route of this bacterium (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the level of efficiency, its high cost and side effects related, several researches have been carried out on natural products, either of vegetal or animal origin, aiming the detection and characterization of chemical compounds with antimicrobial and anti-inflammatory properties (Carson & Riley, 2003;Bonacorsi et al, 2009;Ayala et al, 2014). Plant and honey extracts are among the most attractive sources of new drugs and have shown promising results in gastric ulcer treatment, whose reduction rate, from the beginning of the treatment, serves as a marker of cure (Bonacorsi et al, 2009;Keenan et al, 2010).…”
Section: Antimicrobial and Anti-inflammatory Activities Of Apis Mellimentioning
confidence: 99%
“…Honey is a food supplement which currently has received an increment in commercial consumption, mainly due to the scientific validation of its several beneficial properties to health (Keenan et al, 2010). Such nutraceutical product presents high carbohydrate content, elevated antioxidant activity, as well as expressive antimicrobial activity; it has already been tested in vitro against H. pylori, showing an activity more efficient than some antibiotics commonly indicated (Duarte, 2009;Ayala et al, 2014).…”
Section: Antimicrobial and Anti-inflammatory Activities Of Apis Mellimentioning
confidence: 99%